The infringement of truthfulness principle in radio spot according to the Spanish code of conduct - Muela Molina, Clara (2022)
The objective of this investigation is to identify and examine the characteristic segments that channel a type of discourse in the form of radio spots that infringes the Spanish advertising code of conduct. The work is focused on one of the most important principles for the consumer: that of truthfulness. The different types of misleading advertising have been analysed by means of factor analysis and its subsequent interpretation, based on a representative sample of radio spots that takes into account their broadcast frequency.